Asynchronous Digital Approach for Advancing Learners' Foreign Language Proficiency - Shehada, Suzan; Qassrawi, Rania; Abed , Tagreed; Abu Zeed, Amira; Qarash, Fatima (Forum for Linguistic Studies, 2025)
In today's technology-driven era, language education has increasingly integrated online learning as an essential component, utilizing either synchronous or asynchronous modalities. This study examined the effectiveness of asynchronous digital instruction in enhancing students' language proficiency (listening and speaking proficiency), in addition to exploring their perceptions of this instructional approach. Through employing a mixed-methods design, the research combined quantitative and qualitative methods to provide a comprehensive understanding of the impact of asynchronous language learning activities compared with traditional face-to-face instruction. A quasi-experimental design was implemented with 120 A2-level English students at Birzeit University during the second semester of the 2024/2025 academic year. Participants were divided into two groups: an experimental group using interactive digital modules on Moodle, and a control group receiving conventional in-class instruction. Pre- and post-tests were implemented to measure students' language proficiency in listening and speaking, using a standardized Cambridge Press listening test and a CEFR-aligned speaking task assessed through structured rubrics. Additionally, an open-ended survey was administered to elicit qualitative insights from the experimental group about their asynchronous learning experience. Findings revealed that asynchronous instruction significantly improved students' listening skills, particularly inference-making, identifying details, understanding main ideas, and reasoning. In speaking, statistically significant gains were also observed in content relevance, vocabulary, spoken grammar and fluency. Besides, it was indicated from the qualitative results that asynchronous modules and activities offered students greater flexibility, autonomy, and accessibility. Students appreciated the reduced anxiety and personalized feedback that supported confident participation. However, students also highlighted challenges such as technological limitations, lack of real-time interaction, and the need for increased self-motivation.